How badly did it hit? Self-assessed emotional shock upon prostate cancer diagnosis and psychological well-being: a follow-up at 3, 12, and 24 months after surgery. (3rd July 2017) - Stinesen Kollberg, Karin; Wilderäng, Ulrica; Thorsteinsdottir, Thordis; Hugosson, Jonas; Wiklund, Peter; Bjartell, Anders; Carlsson, Stefan; Stranne, Johan; Haglind, Eva; Steineck, Gunnar
Abstract: Background: We were interested in examining if there was a link between self-assessed emotional shock by prostate cancer diagnosis and psychological well-being at 3, 12, and 24 months after surgery. Material and methods: Information was derived from patients participating in the LAPAroscopic Prostatectomy Robot Open (LAPPRO) trial, Sweden. We analyzed the association between self-assessed emotional shock upon diagnosis and psychological well-being by calculating odds ratios (ORs). Results: A total of 2426 patients (75%) reported self-assessed emotional shock by the prostate cancer diagnosis. Median age of study participants was 63. There was an association between emotional shock and low psychological well-being after surgery: adjusted OR 1.7: (95% confidence interval [CI]), 1.4–2.1 at 3 months; adjusted OR 1.3: CI, 1.1–1.7 at 12 months, and adjusted OR 1.4: CI, 1.1–1.8 at 24 months. Among self-assessed emotionally shocked patients, low self-esteem, anxiety, and having no one to confide in were factors more strongly related with low psychological well-being over time. Conclusion: Experiencing self-assessed emotional shock by prostate cancer diagnosis may be associated with low psychological well-being for up to two years after surgery. Future research may address this high rate of self-assessed emotional shock after diagnosis with the aim to intervene to avoid this negative experience to become drawn out.